Spectrum Sensing Cognitive Radio For Opportunistic Access Environments Based Trust Management - Nilavazhaki, T; Sathish Kumar, G (International Journal of Computer Sciences and Engineering, 2025)
Cognitive Radio System has emerged as a arrangement to the growing range scarcity furthermore, inefficiency problems. However, Cognitive Radio Systems face execution furthermore, security bottlenecks due to lack of memory furthermore, boundless computational capabilities. This issue could be solved if we make use of Cloud as a focal element for storing range accessibility data furthermore, handling of the range accessibility data furthermore, correctly map the region of the unauthorized client to that of the accessible range bands. We will be considering only those range groups for correspondence where the primary customers are absent. If the authorized client is detected, we shall vacant that bands, furthermore, move to another unmoving range bands, that matches our requirements. Admittance will be based on FCFS premise furthermore, at the same time the Quality of Administration necessities (in terms of data rate) of the unauthorized customers will satisfied.